Mediação pedagógica com apoio de material didático para Educação de Jovens e Adultos - Couto, Maria Aparecida [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
In face of the results of scientific studies and based on experience reports on literacy classrooms of youth and adult education, the work related to teaching practice needs to have meaning and significance to the student. Therefore, for that purpose, it becomes necessary to realize a pedagogical meditation which is directed towards the social practices of reading and writing, considering the affective dimension in teacher-student and teaching-learning relationships. Intending to plan and propose pedagogical materials that meet the specific characteristics of young and adult learners, this research generally strives to empirically explore how has the working teacher’s mediation on youth and adult education (EJA) occurred and how it may occur, proposing a specific course material. In this direction, it presents as specific goals: a) to observe, report and analyze the context in which the mediation in three literacy classes for youth and adults occurs; b) through educators, carry the previous survey of the generative words (in alphabetical order) that have been the most worked on in their literacy classes for youth and adults; c) to produce didactic material meant for alphabetization, containing representative images of generator words, meaningful phrases, and some possible activities. Under the qualitative approach, the research was carried on in a school of youth and adults, in which thirty-eight educators and eighteen learning students took part of. It has included the following data-collecting tools: field diary meant for registering the classroom observations; appointment form for generator words, and digital image techniques for production and selection of representative photographs of the cited generator words. The obtained results, under the systematic observation of classrooms, show that the current pedagogical praxis of the schooling unit makes use of multiple methodologies, based on the historical-cultural approach, as well as the traditional one. However, it is possible to notice that the constant presence of Freire's approach, based on dialogue, affection and humanization between teachers and students, as well as the enhancement of knowledge and popular culture brought by the students upon entering school. Also as a result of the current research, this author has developed, in the in integrated product to this thesis, illustrated didactic material for the students (e-book) and containing orientations for the educators, being worth mentioning that all of said illustrations were validated by the students who took part in the present research.

Frente aos resultados dos estudos científicos e a partir de relatos de experiência em salas de aula de alfabetização de jovens e adultos, entende-se que o trabalho referente à prática pedagógica precisa ter sentido e significado para o educando. Assim, torna-se necessário, para o letramento, uma mediação pedagógica que seja direcionada às práticas sociais da leitura e da escrita, considerando a dimensão afetiva nas relações educador-educando no processo de ensino-aprendizagem. Com intenção de planejar e propor materiais pedagógicos, que atendam às especificidades dos educandos jovens e adultos, esta pesquisa tem como objetivo geral explorar, empiricamente, como tem ocorrido e pode vir a ocorrer a mediação pedagógica do educador atuante na Educação de Jovens e Adultos (EJA), propondo um material didático específico. Nessa direção, apresenta como objetivos específicos: a) observar, relatar e analisar o contexto em que se dá a mediação pedagógica em três classes de alfabetização de jovens e adultos; b) realizar, com os educadores, o levantamento prévio das palavras geradoras (em ordem alfabética) mais trabalhadas em suas salas de alfabetização de jovens e adultos; c) produzir um material didático para alfabetização contando com imagens representativas das palavras geradoras, frases significativas e algumas possibilidades de atividades. Sob a abordagem qualitativa, a pesquisa foi realizada em uma escola de jovens e adultos, da qual participaram trinta e oito educadores e dezoito educandos. Contou com os seguintes instrumentos de coleta de dados: diário de campo para registro das observações em sala de aula; formulário de apontamento para palavras geradoras e técnica de imagem digital para produção e seleção de fotografias representativas das palavras geradoras apontadas. Os resultados obtidos, pela observação sistemática nas salas, apontam que a práxis pedagógica atual da unidade escolar faz uso de múltiplas metodologias, embasadas na abordagem histórico-cultural e também na tradicional. Contudo, é perceptível a presença constante da abordagem freireana, tendo por base o diálogo, a afetividade e a humanização entre educadores e educandos, com a valorização dos saberes e da cultura popular que os educandos trazem ao ingressarem na escola. Também como resultado da presente pesquisa, esta autora desenvolveu, no produto integrante à dissertação, material didático ilustrado para os educandos (e-book) e com orientações para os educadores, ressaltando que todas as ilustrações nele constantes foram validadas pelos educandos participantes da pesquisa.
Pedagogical Mediation With the Support of Didatic Material for the Education of Youth and Adults
Keywords: Alfabetização de Jovens e Adultos; Material didático; Mediação pedagógica; Pedagogical meditations; Literacy for Youth and Adults; Didactic material